2019
DOI: 10.3390/ijgi9010014
|View full text |Cite
|
Sign up to set email alerts
|

UAV-Based Structural Damage Mapping: A Review

Abstract: Structural disaster damage detection and characterization is one of the oldest remote sensing challenges, and the utility of virtually every type of active and passive sensor deployed on various air- and spaceborne platforms has been assessed. The proliferation and growing sophistication of unmanned aerial vehicles (UAVs) in recent years has opened up many new opportunities for damage mapping, due to the high spatial resolution, the resulting stereo images and derivatives, and the flexibility of the platform. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 89 publications
0
56
0
7
Order By: Relevance
“…Automated building damage classification has received increased attention during the last several years both from practitioners [15][16][17] and from researchers [18,19]. Models have been developed that forecast the building damage before the disaster arrives or that predict the building damage after the disaster has struck.…”
Section: Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Automated building damage classification has received increased attention during the last several years both from practitioners [15][16][17] and from researchers [18,19]. Models have been developed that forecast the building damage before the disaster arrives or that predict the building damage after the disaster has struck.…”
Section: Previous Researchmentioning
confidence: 99%
“…The first studies on automatically predicting damage from remotely sensed data mainly explored the use of texture-and segmentation-based methods (e.g., [23,[29][30][31]) and showed that while it is possible to automatically detect damage, results in performance are not always satisfying [18]. Due to the complex nature of features indicating damage and with the increased popularity of machine learning, research started to be conducted on the use of machine learning techniques for automatic classification, especially focusing on CNNs.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, the use of unmanned aerial vehicles (UAVs) is one of the techniques accepted by experts to achieve accurate, high-quality, and fast mapping data [ 16 ]. In recent years, photogrammetric point clouds and especially UAV point clouds have been used in different modeling and reconstruction applications [ 17 , 18 , 19 ], and UAV point clouds are used to obtain surveying data for analyzing, detecting and reconstructing railways. By using UAV technology, rail mapping projects can be controlled from outside the railway area, thus preventing the disruption of rail services as well as saving people from danger [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Advances intechnologyandavailabilityhaveboosted the number of applications in many sectors but especially in regions with local and regional dynamic features. Just a few innovative and successful examples of UAS-based monitoring are glacier monitoring for ice flow and mass wasting (Immerzeel et al, 2014;Kraaijenbrink et al, 2016), landslide dynamics monitoring and surface deformation (McKean, 2004;Niethammer et al, 2012;Lucieer et al, 2014;Giordan et al, 2020;Karantanellis et al, 2020), dune dynamics (Ruessink et al, 2018), flood risk mapping (Hashemi-Beni et al, 2018), night-time light monitoring as proxy for economic activity (Li et al, 2020), public health care and health-related services (Amukele et al, 2015;Scalea, 2020), and post-disaster damage assessment (Kerle et al, 2019;Liao et al, 2020).…”
mentioning
confidence: 99%